Management of the Aging Forehead and Brow - Langsdon, Phillip; Petersen, Dana (Facial Plastic Surgery, 2014)
The appearance of the forehead and brow conveys both a state of aging as well as the dynamic status of human emotion. Maintaining a youthful and pleasant appearance of this region is often integral to facial rejuvenation. Conditions that are often addressed include transverse rhytids and glabellar frown lines, ptotic eyebrows, skin deterioration, and volume loss. Surgical treatments to improve the forehead/brow might be open, endoscopic or combined. Common nonsurgical methods used to improve the region include neuromodulation, volume replacement, ablative and nonablative skin resurfacing, as well as phototherapy. Whatever treatments might be indicated, aim is to achieve optimum and natural-looking results.
Keywords: forehead lift; brow lift; neuromodulation